Service of Bartenders in Making A Cocktail to Improve Guest Satisfaction in Sindhu Restaurant Grand Palace Hotel Sanur Bali - Wichitakani Wahyu Cakraningrat, Putu Bagus; Wirawan, I Wayan; ., Marina; Satia Negara, I Made Weda (Jurnal Manajemen Pelayanan Hotel, 2024)
This research aims to explore the process of making cocktail drinks by bartenders at Sindhu Restaurant, GrandPalace Hotel Sanur, Bali, as well as understanding the techniques and creativity applied in creating attractiveand high-quality drinks. The research method used is qualitative, the collection method in this research usesliterature study, direct observation and in-depth interviews with the bartender on duty. The results showedthat bartenders at Sindhu Restaurant combine detailed technical skills with artistic elements to producecocktail drinks that are not only delicious but also visually appealing. The use of local and fresh ingredients, aswell as in-depth knowledge of various mixing techniques, are key factors in their success.In addition, this research also highlights the importance of the interaction between bartenders and customersin creating a unique and personalised drinking experience. The bartenders at Sindhu Restaurant not only actas drink makers, but also as guides who are able to customise cocktails to customers' individual preferences.This increases the level of customer satisfaction and strengthens the restaurant's reputation as a place thatprovides high-quality service. The conclusion of this study confirms that the skills and creativity of bartendersare important elements in the hospitality industry, contributing significantly to customer satisfaction.Keywords: Service, Guest Satisfaction, Making Cocktail.